2021
DOI: 10.1186/s12884-021-04337-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant during the COVID-19 pandemic: an exploration of patients’ lived experiences

Abstract: Background Infectious outbreaks are known to cause fear and panic. Exploration of pregnant individuals’ psychosocial condition using a qualitative lens during an infectious outbreak is limited. In this study we explore pregnant individuals’ lived experiences as well as their psychological and behavioural responses during COVID-19 with the goal of providing useful strategies from the patient’s perspective to enable health care providers to help pregnant patients navigate this and future pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 54 publications
(51 reference statements)
1
58
1
1
Order By: Relevance
“…A minority of respondents felt pandemic changes had a positive effect on their mental well-being. Infection mitigation plans produced an environment where families could have more time at home, with fewer parents leaving the house for work and children for school or daycare, and fewer social obligations, which is supported by other qualitative findings on postpartum experiences during the COVID-19 pandemic [30]. Some expressed relief in not having to entertain visitors during the postpartum period.…”
Section: Loss Of Support and Mental Healthmentioning
confidence: 56%
See 2 more Smart Citations
“…A minority of respondents felt pandemic changes had a positive effect on their mental well-being. Infection mitigation plans produced an environment where families could have more time at home, with fewer parents leaving the house for work and children for school or daycare, and fewer social obligations, which is supported by other qualitative findings on postpartum experiences during the COVID-19 pandemic [30]. Some expressed relief in not having to entertain visitors during the postpartum period.…”
Section: Loss Of Support and Mental Healthmentioning
confidence: 56%
“…Others have also reported qualitative data about the impact of COVID-19 on prenatal care using different survey instruments or via semi-structured interviews [29][30][31][32]. Javid et al identified similar structural changes in healthcare and behavioral changes to reduce disease transmission (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of social support as a protective factor during the pandemic has been reported. 23 The importance of social support and its “buffering effect” was also seen in the SARS data as those that reported more social support were less depressed. 4 Finally, individuals who exercised at least weekly or more were significantly less likely to have depression, anxiety or stress, similar to a previous study.…”
Section: Discussionmentioning
confidence: 89%
“…Further, competing media messaging and medical advice has led to increased vaccine hesitancy among pregnant people ( Ayhan et al, 2021 ; Iacobucci, 2021 ). The scant literature on pregnant people’s experiences during the pandemic has revealed that pregnant individuals report heightened anxiety and depression, compared to pre-pandemic cohorts and non-pregnant individuals ( Caparros-Gonzalez & Alderice, 2020 ; Harrison et al, 2021 ; Kolker et al, 2021 ; Schaal et al, 2021 ). However, to date, no research has explored pregnant people’s experiences of their bodies and body image during the pandemic.…”
Section: Introductionmentioning
confidence: 99%